2012
DOI: 10.1111/j.1365-2966.2012.21214.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved observations of warm ionized gas and feedback in local ULIRGs★

Abstract: We present Very Large Telescope (VLT)/VIsible MultiObject Spectrograph integral field unit (VIMOS‐IFU) emission‐line spectroscopy of a volume‐limited sample of 18 southern ultraluminous infrared galaxies (ULIRGs) selected with z < 0.09 and δ < 10. By covering a wide range of ULIRG types, including many systems that have received very little previous attention, this data set provides an important set of templates for comparison with high‐redshift galaxies. We employed an automated Gaussian line‐fitting programm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
130
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 162 publications
(383 reference statements)
18
130
0
3
Order By: Relevance
“…A number of authors have examined optical emission lines for signs of outflows as well. Arribas & Colina (2003) found no evidence of outflows in their INTEGRAL observations (although they do suggest an inflowing component to the southwest); Westmoquette et al (2012) also find no evidence for outflows in their VIMOS data. However, fit multiple components to the emission lines in their optical long-slit spectra and produce measurements of velocity offset (∼-100 km s −1 from systemic) and velocity dispersion (∼100 km s −1 ) for the shocked components, which they sum together to produce an estimated outflow velocity of 200 km s −1 ; they also use emission line ratios and shock models to infer shock velocities ranging from 50-600 km s −1 .…”
Section: Introductionmentioning
confidence: 93%
“…A number of authors have examined optical emission lines for signs of outflows as well. Arribas & Colina (2003) found no evidence of outflows in their INTEGRAL observations (although they do suggest an inflowing component to the southwest); Westmoquette et al (2012) also find no evidence for outflows in their VIMOS data. However, fit multiple components to the emission lines in their optical long-slit spectra and produce measurements of velocity offset (∼-100 km s −1 from systemic) and velocity dispersion (∼100 km s −1 ) for the shocked components, which they sum together to produce an estimated outflow velocity of 200 km s −1 ; they also use emission line ratios and shock models to infer shock velocities ranging from 50-600 km s −1 .…”
Section: Introductionmentioning
confidence: 93%
“…In spite of previous negative evidence of an outflow in the ionized gas (Westmoquette et al 2012;Rupke & Veilleux 2013), Arribas et al (2014) report the detection of an outflowing component, based on very high signal-to-noise ratio Hα spectroscopy. The maximum velocities of the ionized outflow reach moderate values of up to v − v sys ∼ −300 km s −1 and the estimated outflow rate for the ionized gas is ∼16 M yr −1 (Colina, private communication).…”
Section: Iras 17208-0014mentioning
confidence: 99%
“…Only very recently spatially resolved optical, far infrared and mm spectroscopic studies convincingly showed evidences for the existence of such processes in the form of the predicted energetic outflows in ULIRGs with Seyfert nuclei in the local Universe (e.g. Feruglio et al 2010;Fischer et al 2010;Rupke & Veilleux 2011;Villar-Martín et al 2011;Rodríguez-Zaurín et al 2013;Zhang et al 2011;Westmoquette et al 2012;Rupke & Veilleux 2013;Harrison et al 2014;McElroy et al 2014; see also Elvis 2000 for a discussion on the ubiquitous presence of winds in the AGN structure).…”
Section: Introductionmentioning
confidence: 99%